2021
DOI: 10.1159/000518892
|View full text |Cite
|
Sign up to set email alerts
|

What’s New with Endoscopic Treatments for Early Gastric Cancer in the “Post-ESD Era”?

Abstract: <b><i>Background:</i></b> Endoscopic treatments for gastric cancers have still been progressing even after the great success of endoscopic submucosal dissection (ESD). <b><i>Summary:</i></b> In further advancements of ESD, safe and less-invasive procedures are challenged by managing postoperative bleeding, one of the major adverse events in ESD. Covering the mucosal defect after removal of lesions appears reasonable and effective for preventing delayed bleeding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…However, despite the effectiveness of ESD, its associated high rate of heterochronic recurrence needs to be addressed [6]. Studies have shown that recurrence usually occurs near the original tumor site, highlighting the need to assess and predict possible risk factors for recurrence [7][8][9]. A thorough understanding of these risk factors will help develop personalized surveillance plans and treatment strategies to reduce the recurrence risk and improve treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the effectiveness of ESD, its associated high rate of heterochronic recurrence needs to be addressed [6]. Studies have shown that recurrence usually occurs near the original tumor site, highlighting the need to assess and predict possible risk factors for recurrence [7][8][9]. A thorough understanding of these risk factors will help develop personalized surveillance plans and treatment strategies to reduce the recurrence risk and improve treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%